Vegetarian diet, food substitution, and nonalcoholic fatty liver - Tina H Chiu; Ming-Nan Lin; Wen-Harn Pan; Yen-Ching Chen; Chin-Lon Lin (Tzu Chi Medical Journal)
Objectives: Vegetarian diets have been shown to improve insulin resistance and reduce body weight, but the effects on nonalcoholic fatty liver require further confirmation. We aim to investigate the association between vegetarian diets, major food groups, and nonalcoholic fatty liver, and to compare the degree of liver fibrosis between vegetarians and nonvegetarians in those with fatty liver. Materials and Methods: We analyzed cross-sectional data from the Tzu Chi Health Study which included 2127 nonvegetarians and 1273 vegetarians who did not smoke or habitually drink alcohol and had no hepatitis B or hepatitis C. Fatty liver and liver fibrosis were determined using ultrasonography and the nonalcoholic fatty liver disease fibrosis score, respectively. Diet was assessed through a validated food frequency questionnaire. Results: Vegetarian diets were associated with lower odds of fatty liver (odds ratio = 0.79, 95% confidence interval: 0.68–0.91) after adjusting for age, gender, education, history of smoking and alcohol drinking. Adjustment for body mass index (BMI) attenuated the protective association. Vegetarians had less severe fibrosis than nonvegetarians. Replacing a serving of soy with a serving of meat or fish was associated with 12%–13% increased risk, and replacing a serving of whole grains with a serving of refined grains, fruits, and fruit juice was associated with 3%–12% increased the risk of fatty liver. Conclusion: Vegetarian diets, replacing meat and fish with soy, and replacing refined carbohydrates with whole grains, may be inversely associated with nonalcoholic fatty liver related to BMI.